Rancang Bangun Sistem Manajemen Waktu Akses Internet menggunakan Mikrotik di Lingkungan Pondok Pesantren Golden Star - Rudi Hartono; Nuari Anisa Sivi (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2024)
The increasing demand for internet access at Pondok Pesantren Golden Star has supported the students’ learning process; however, uncontrolled usage may disrupt discipline, worship activities, and the daily routines within the pesantren environment. To address this issue, this study aims to design and develop an internet access time management system using Mikrotik, capable of regulating and restricting internet usage according to schedules determined by the institution. The primary objective of this research is to produce an automated and effective access control system that aligns with the policies of the pesantren. This study employs the Network Development Life Cycle (NDLC) methodology, which consists of the stages of analysis, design, simulation, prototyping, implementation, monitoring, and management. During the implementation stage, the Mikrotik configuration involved IP addressing, DHCP server setup, firewall filter rules, and time-based schedulers. The results indicate that the system successfully restricts student internet access to the period between 06:00 and 17:00, while automatically blocking access outside these hours. Testing confirms that the time-based restriction feature operates consistently and reliably, meeting the institution's requirements for fostering a more conducive environment for learning and worship. In conclusion, the Mikrotik-based internet access time management system is effective, easy to maintain, and has the potential for further development in accordance with the needs of the pesantren